Prognostic value of admission heart rate in patients with ST-segment elevation myocardial infarction: Role of Type 2 diabetes mellitus - Han, Zhang (BioMed Central, 2012)
BACKGROUND: It’s unknown whether the prognostic value of admission heart rate (HR) was different in patients with ST-segment elevation myocardial infarction (STEMI) with or without concomitant type 2 diabetes mellitus (T2DM). METHODS: Consecutive STEMI patients who presented within 12 hours of symptom onset were recruited from 274 hospitals in China. Participants were stratified into quartiles by admission HR. Baseline characteristics, current therapeutic recommenda- tions, laboratory biochemical tests, 30-day all-cause mortality and Cardiovascular Events (CVE, including all-cause death, reinfarction and stroke) were compared across admission HR quartiles. RESULTS: We evaluated 7294 STEMI patients, of these 820 (11.2%) had known T2DM. The admission HR quartile stratification was significantly associated with all-cause mortality and CVE regardless of T2DM status (P < 0.001 both for survival and CVE). After adjusted other risk factors, in patients without T2DM, comparing with HR <66 b.p.m., the increase of HR level was associated with worse prognosis (P < 0.05). In patients with T2DM, the hazard ratios for 30-day CVE were 1.75 (95%CI), 1.92 (95%CI), 3.00 (95%CI) in the HR of 66–76 b.p.m., 77–88 b.p.m., and >88 b.p.m., respectively. Results were similar for 30-day all-cause mortality, but the hazard ratios in Q2 (P = 0.139 and P =0.086 for survival and CVE, respectively) and Q3 groups were non-significant (P = 0.072 and P =0.033 for survival and CVE, respectively). There was a significant interaction effect of HR and T2DM on 30-day CVE mortality (P = 0.035), which was not found on all-cause mortality (P = 0.126). CONCLUSION: Admission heart rate was an important risk factor of 30-day all-cause mortality and CVE in patients with STEMI with or without T2DM. However, the predictive effect was modified by T2DM.